PEMETAAN PENELITIAN TEACHING GAMES FOR UNDERSTANDING (TGfU) TAHUN 2000 - 2010 - Satyaning Rahayu, Jati (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
The study is aimed to map the researches on Teaching Games for Understanding (TGfU). The researches mappedare those conducted in 2000-2010. Design of the study is descriptive, with survey method and using quantitativeapproach. The subject is 25 researches on Teaching Games for Understanding (TGfU) in 2000-2010. Techniquefor collecting data is by using documentation technique. Instrument used is documentation guideline. Validation ofthe instrument is by using expert judgment. In documentation guideline, there is a coding in assisting the analyticalprocess. The coding is the title, researcher (name of researcher, institution, and country), year, purpose, approach,design, and sample/subject, method for collecting data, analytical data technique, and conclusion. Analytical datatechnique is a document analysis which is then quantitatively made it into percentage. Result of the mapping showsthat researches on TGfU has been conducted many times in many countries. 245 of the researchers come fromAustralia. 28% of the researches are conducted in 2003. 68% of the approaches used in the research are qualitativeapproach. Design of researches on TGfU is in variation. Survey and case study method is used in 28% of theresearches. 24% of the researches use experiment and 20% of researches use contain analysis. Researches usingstudents as sample/subject is 48%. 20% of collecting data methods uses test and observation. For analytical datatechnique, 72% uses qualitative descriptive.Keywords: Mapping, Research, Teaching Games for Understanding (TGfU)